Anticancer effects of radiation therapy combined with Polo-Like Kinase 4 (PLK4) inhibitor CFI-400945 in triple negative breast cancer. (August 2021) - Parsyan, Armen; Cruickshank, Jennifer; Hodgson, Kelsey; Wakeham, Drew; Pellizzari, Sierra; Bhat, Vasudeva; Cescon, David W.
Abstract: Development of novel multimodality radiotherapy treatments in metastatic breast cancer, especially in the most aggressive triple negative (TNBC) subtype, is of significant clinical interest. Here we show that a novel inhibitor of Polo-Like Kinase 4 (PLK4), CFI-400945, in combination with radiation, exhibits a synergistic anti-cancer effect in TNBC cell lines and patient-derived organoids in vitro and leads to a significant increase in survival to tumor endpoint in xenograft models in vivo, compared to control or single-agent treatment. Further preclinical and proof-of-concept clinical studies are warranted to characterize molecular mechanisms of action of this combination and its potential applications in clinical practice. Highlights: PLK4 inhibitor CFI-400945, combined with radiation, shows synergistic antiproliferative activity in immortalized breast cancer cell lines. CFI-400945 in combination with radiation shows synergistic antiproliferative activity in breast cancer patient-derived organoids. In MDA-MB-231 xenograft mice, CFI-400945 sensitizes to radiation and significantly improves survival to the tumour endpoint.